Pengaruh Etika Bisnis Islam terhadap Kinerja Bank (Studi pada Bank BRI Syariah di Malang) - Nurtjahjani, Fullchis (Universitas Brawijaya, Indonesia, 2011)
This research has a purpose to know The Influence of Islamic Business Ethics to the Bank Performance. It use a linier regression analysis, double regression analysis and route analysis. The results show that the over resources using make joint venture could not give the great contribution for syariah bank performances. Actually, Islamic Business Ethics should improve the Syariah Bank Performances. The capabillity of Syariah Bank Entrepreneur to aplicate Islamic Business Ethics by Joint Venture, Intermediary Organization, Free Interest System, the over resources using, and also the sharing profit model could give a satisfaction to the bank customer. It make the syariah bank performances rise continously.